The impact of climate change on the well‐being and lifestyle of a First Nation community in the western James Bay region. (30th September 2013) - Tam, Benita Y.; Gough, William A.; Edwards, Vicky; Tsuji, Leonard J. S.
<x xml:space="preserve">Abstract</x> Through the use of traditional environmental knowledge (TEK), the impacts of climate change on the Fort Albany First Nation community are explored. Thirty‐nine community members were interviewed using a semi‐directive interview format to gather knowledge about their observations of local environmental and climatic change and the significance of these changes. Thematic analysis, cluster analysis, and concept mapping were applied to analyze interview transcriptions. A second round of interviews was conducted to obtain feedback on the themes and concepts that emerged from the first round of interviews. Community members indicated that there have been noticeable changes in the timing of seasons, snow type, and total snowfall, with an increase in extreme weather events. These changes have impacted animal behaviour, traditional harvesting activities, and the winter road, which have led to socio‐economic and well‐being issues. The community has exhibited strength in adapting to ongoing changes in the environment; however, their ability to adapt to climate change in the future is not certain.